2013
DOI: 10.1097/bcr.0b013e31827e6363
|View full text |Cite
|
Sign up to set email alerts
|

Using Anonymized, Routinely Collected Health Data in Wales to Estimate the Incidence of Depression After Burn Injury

Abstract: Burn injuries are associated with depression. Patients show variable incidence of postburn depression. The purpose of this study was to use anonymized, routinely collected health-related data in Wales (United Kingdom) to estimate the incidence of depression postburns. The incidence of postburn depression was estimated using routinely collected health data of complete years (1999-2007) from all general practitioner surgeries in Swansea and all National Health Service hospitals in Wales. This had been collected,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…By understanding the performance of the different algorithms we gain a lot of insight into their potential use for research. We are now including the CMD as mental health outcomes in studies across a range of areas, including the environment, housing, suicide and for clinical research [ 47 , 52 54 ]. We plan to externally validate the algorithms developed to assess CMD in children and young people using age-appropriate survey data.…”
Section: Discussionmentioning
confidence: 99%
“…By understanding the performance of the different algorithms we gain a lot of insight into their potential use for research. We are now including the CMD as mental health outcomes in studies across a range of areas, including the environment, housing, suicide and for clinical research [ 47 , 52 54 ]. We plan to externally validate the algorithms developed to assess CMD in children and young people using age-appropriate survey data.…”
Section: Discussionmentioning
confidence: 99%
“…In other study, symptoms of moderate to severe depression was observed in 54% of the patients within the first month and a follow up during the second month showed that 43% of them still meet the criteria for depression with unchanged severity [11]. These mental consequences could be long lasting as incidence of depression is reported to be 5.9% within 5 years after the burn injury, being 7.4% in female patients and 4.3% in male patients [12]. Major depressive disorder (MDD) may deteriorate the condition of patients by increasing pain feeling and decreasing physical functioning of these patients [1].…”
Section: Introductionmentioning
confidence: 97%
“…Some studies indicated that inflammation involved in the PTSD and depression, and treatment involving exogenous inflammatory factors may also induce depression. [5][6][7] The exact mechanism is not clear. In this study, we aim to investigate the expression of inflammatory factors in burn injury patients with PTSD and depression.…”
mentioning
confidence: 99%